Dielectric spectroscopy measurements on kaolin suspensions for sediment concentration monitoring. (June 2018) - Mishra, P.N.; Bore, T.; Jiang, Y.; Scheuermann, A.; Li, L.
Highlights: Dielectric spectroscopy aided suspended sediment concentration monitoring. Correlations among frequency, permittivity and suspended sediment concentration. Dielectric mixing equations for estimating suspended sediment concentration. Statistical ranking model for judging relative efficiency of the mixing equations. Abstract: Sedimentation along with consolidation processes dictate the in situ engineering and hydraulic behavior of a particulate system such as soil. With this in view, the present investigation discusses about the application of dielectric measurements in relation to sediment concentration measurements for fine grained soils. An in-house set up comprising of open ended coaxial probes and vector network analyzer has been used to measure the dielectric behavior of kaolin suspensions in tap and deionized water. These have been further analyzed to furnish suspended sediment concentration, pore water conductivity and shape factors utilizing Complex Refractive Index Model (CRIM) and Bruggeman–Hanai–Sen (BHS) model, through the implementation of an optimization scheme. Furthermore, measured and estimated suspended sediment concentrations showed good agreement with each other in terms of statistical parameters, and a ranking of models approach reliant on three statistical criteria revealed that, CRIM outperforms BHS model for estimating sediment concentrations.